2020
DOI: 10.3390/biom10050788
|View full text |Cite
|
Sign up to set email alerts
|

Different Impacts of MucR Binding to the babR and virB Promoters on Gene Expression in Brucella abortus 2308

Abstract: The protein MucR from Brucella abortus has been described as a transcriptional regulator of many virulence genes. It is a member of the Ros/MucR family comprising proteins that control the expression of genes important for the successful interaction of α-proteobacteria with their eukaryotic hosts. Despite clear evidence of the role of MucR in repressing virulence genes, no study has been carried out so far demonstrating the direct interaction of this protein with the promoter of its target gene babR encoding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…In accordance with the proteomic results ( Figure 1 ), transcripts for genes hdeA, omp25d , and BOV_A0299 were overrepresented in the Δ mucR mutant of B. ovis PA when compared to the parental strain and the complemented mutant ( Figure 5 ); the results were also reproduced in B. canis RM6/66 ( Table 4 ). Considering the results described in B. abortus 2308 ( 20 , 33 ), genes BOV_0982 and BOV_0183 , the latter coding for the LuxR family quorum sensing transcriptional regulator blxR ( 34 ) also named babR ( 35 ), were also included in the transcriptomic analysis. In B. abortus 2308, overexpression of the corresponding orthologs BAB1_0190 and BAB1_1035 in the Δ mucR mutant has been associated to the demonstrated direct binding of MucR to their promoter region ( 20 , 33 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with the proteomic results ( Figure 1 ), transcripts for genes hdeA, omp25d , and BOV_A0299 were overrepresented in the Δ mucR mutant of B. ovis PA when compared to the parental strain and the complemented mutant ( Figure 5 ); the results were also reproduced in B. canis RM6/66 ( Table 4 ). Considering the results described in B. abortus 2308 ( 20 , 33 ), genes BOV_0982 and BOV_0183 , the latter coding for the LuxR family quorum sensing transcriptional regulator blxR ( 34 ) also named babR ( 35 ), were also included in the transcriptomic analysis. In B. abortus 2308, overexpression of the corresponding orthologs BAB1_0190 and BAB1_1035 in the Δ mucR mutant has been associated to the demonstrated direct binding of MucR to their promoter region ( 20 , 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…Considering the results described in B. abortus 2308 ( 20 , 33 ), genes BOV_0982 and BOV_0183 , the latter coding for the LuxR family quorum sensing transcriptional regulator blxR ( 34 ) also named babR ( 35 ), were also included in the transcriptomic analysis. In B. abortus 2308, overexpression of the corresponding orthologs BAB1_0190 and BAB1_1035 in the Δ mucR mutant has been associated to the demonstrated direct binding of MucR to their promoter region ( 20 , 33 ). Both genes were also upregulated in the Δ mucR mutant of B. ovis PA ( Figure 5 ) and in B. canis RM6/66 ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some specific SNPs clusters resembling barcodes or fingerprints were identified in Brucella genotypes from terrestrial and marine mammals [ 27 ]. This differential pattern may be relevant since SNP variations could influence the expression of neighbor coding sequences (CDS) or RNA coding genes, contributing to niche adaptation [ 103 , 139 ].…”
Section: Brucella Speciation and Host Preferencmentioning
confidence: 99%
“…In Brucella strains, previous studies have also demonstrated that MucR protein is involved in resistance to environmental stresses, such as acidic stress, oxidative stress, detergent, cationic peptide, and iron deficiency (9,11). Additionally, previous transcriptomic and microarray analyses have revealed that MucR could directly and indirectly affect the expression of hundreds of genes involved in metabolism, cell wall/envelope biogenesis, replication, and translation (9,12). In recent studies, various target genes, which were directly regulated by MucR protein, were also identified, such as babR, virB genes, bab1_0746, bab1_1035, bab1_1605, and bab1_1893 (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, previous transcriptomic and microarray analyses have revealed that MucR could directly and indirectly affect the expression of hundreds of genes involved in metabolism, cell wall/envelope biogenesis, replication, and translation (9,12). In recent studies, various target genes, which were directly regulated by MucR protein, were also identified, such as babR, virB genes, bab1_0746, bab1_1035, bab1_1605, and bab1_1893 (12,13). Compared to the well-studied MucR protein in smooth-type Brucella strains, no study has been carried out so far to demonstrate the function of MucR protein in B. canis strains.…”
Section: Introductionmentioning
confidence: 99%